A Study on Customer Satisfaction towards Patanjali Products in Theni District - Malarvizhi, J.; Devi, T. Chitra (International Research Journal of Management, IT & Social Sciences, 2018)
Indian consumer segment is broadly segregated into urban and rural markets and is attracting marketers from across the world. Global corporations view India as one of the key markets from where future growth is likely to emerge. Consumers of this millennium have become more concerned about their health and also inclined to maintain the quality of life which is reflected through the preferential consumption of those products that protect the good state of their health as well as provide maximum satisfaction. To purchase a product the customer will go through a process of buying behavior. The choice and usage of a particular brand by the consumer over the time is affected by the quality benefits offered by the brand especially when it comes to the brand of eatable and cosmetics. This study also aims at identifying customerâs satisfaction towards present and expected products from Patanjali.